THE CONTRIBUTION OF PSYCHOLOGICAL FACTORS ON ACADEMIC ACHIEVEMENT OF RURAL STUDENTS IN THE INTERIOR SCHOOLS OF SABAH DIVISION - Getrude C. Ah Gang @ Grace; Crispina Gregory K Han; Lawrence Alan Bansa (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examines the effects of three psychological factors (i.e., academic self-efficacy, psychological well-being & parental supports) on rural students’ academic achievement. The study predicted that the three factors contributed to students’ academic achievement. There were 1586 students from 21 rural schools in the interior division of Sabah involved in this study. A questionnaire with four parts was used to measure all variables. Part A measures the demographic variables (i.e., the current academic achievement, academic level, age, gender, and school); Part B measures the academic self-efficacy. Part C measures parental involvement in the students’ academics, and Part D measures psychological well-being. Hierarchical regression analysis was used to analyse the data. Parental support in students’ academic tasks contributed positively 1% on the variance of students’ academic achievement. In Step 2, when the students’ academic self-efficacy included, both factors (i.e., parental support & academic self-efficacy) contributed 5% on academic achievement. In Step 3, parental support, academic self-efficacy, and psychological well-being contributed positively 7% on academic achievement. The findings showed that parental support, students’ academic self-efficacy, and psychological well-being can be good predictors to academic achievement of rural students. These findings provide positive insights to the relevant authorities, such as the schools department, Sabah Education Department, and the Parent-Teacher Associations, to create relevant academic programs which may give more opportunity for parents to get involved in any relevant academic activities at schools and which may level up the awareness among parents of their role in supporting their children’s academic performance. Besides parental involvement, students’ academic self-efficacy and psychological well-being also need to be taken into consideration by the relevant authorities in enhancing rural students’ academic achievement.